The Ancestral Domain Claim of the Higaunon in Cauyonan, Opol, Misamis Oriental - L. Bracamonte, Nimfa; M. MAJORENOS, GRACE; L. PONCE, SULPECIA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
In the tradition of the Higaunons of Cauyonan, their ancestors came from Lanao and Bukidnon. They were told that Kamayungan Malarugao, Bukidnon and Apo Limbubungan, her husband, was a Muslim. Because of differences in faith, their descendants were separated. The followers of Islam, the Maranaos, settled in Lanao while the Higaunons stayed in Bukidnon. The early Higaunon migrants from Bukidnon went to Dulangan, the old name of Cauyonan, in search for gold. The word Dulangan is from the Higaunon word "dulang" which means gold. Later political developments led to the split of Dulangan into Tumpagon and Cauyonan. The latter derived its name from the word "uyon" which is a Visayan term for "agree." The Council of Datus in this place agreed (gikauyonan) to transfer their settlement to the present site, now called Cauyonan. Previously, the Higaunons in Cauyonan were living in Malungon, an adjacent place.. The genealogy of key informants reveal that the Higanons have lived here for at least six generations, or the equivalent of 240 years, more than enough as a basis for pursuing their ancestral domain claim. Seven ancestors are often men-tioned: Apo Sanditan and Inay Pagote; Apo Manugsal and Inay Ugsal; Apo Gilong and Inay Sugay-ot; Apo Mansalid and Inay Ansalid; Apo Amay Paramata and Inay Paramata, Apo Man-ibog and Inay Ibog, and Apo Manmahunyag and Inay Mahunyag